The preconditioning of explicit group-2 point linear systems with 5 and 9 block diagonals - Daoud, DS; Subasi, D (Gordon Breach Sci Publ Ltd, 1996)
The following paper presents the evaluation of the performance of the preconditioned conjugate gradient through the use of the incomplete matrix decomposition for the explicit group-2 matrices with different numbers of nonzero block diagonals.
Keywords: explicit group-2 finite difference; incomplete matrix decomposition; linear elliptic partial differential equation; Preconditioned Conjugate Gradient method